PHYSA MARMORATA (MOLLUSCA: PHYSIDAE) AS INTERMEDIATE HOST OF ECHINOSTOMA EXILE (TREMATODA: ECHINOSTOMATIDAE) IN BRAZIL - Alves Pinto, Hudson (2012)
Echinostome cercariae with 45 collar spines were found in Physa marmorata Guilding, 1828 collected in a water body located in Belo Horizonte, Minas Gerais, Brazil. Metacercariae were obtained experimentally in Biomphalaria glabrata (Say, 1818) and used to perform the infection of Columba livia Gmelin, 1789. Adult parasites recovered in the small intestine of the pigeons at 14 days after infection were identified as Echinostoma exile Lutz, 1924. The morphology of cercaria of E. exile is described for the first time and P. marmorata is reported as the natural first intermediate host of the parasite.